Experimental Analysis of Water Pressure and Temperature Influence on Atomization and Evolution of a Port Water Injection Spray - Lucio Postrioti; Gabriele Brizi; Gian Marco Finori (Applied Sciences, 2021)
Port water injection (PWI) is considered one of the most promising technologies to actively control the increased knock tendency of modern gasoline direct injection (GDI) engines, which are rapidly evolving with the adoption of high compression ratios and increased brake mean effective pressure levels in the effort to improve their thermal efficiency. For PWI technology, appropriately matching the spray evolution and the intake system design along with obtaining a high spray atomization quality, are crucial tasks for promoting water evaporation so as to effectively cool down the air charge with moderate water consumption and lubricant dilution drawbacks. In the present paper, a detailed experimental analysis of a low-pressure water spray is presented, covering a lack of experimental data on automotive PWI systems. Phase doppler anemometry and fast-shutter spray imaging allowed us to investigate the influence exerted by the injection pressure level and by the water temperature on spray drop size and global shape, obtaining a complete database to be used for the optimization of PWI systems. The obtained results evidence how significant benefits in terms of atomization quality can be obtained by adopting injection pressure and water temperature levels compliant with standard low injection pressure technologies.